"The Talk" and Parenting While Black in America: Centering Race, Resistance, and Refuge. (May 2022) - Anderson, Leslie A.; O'Brien Caughy, Margaret; Owen, Margaret T.
"The Talk" refers to a specific type of racial socialization message that many Black parents have with their children about how to safely conduct themselves when interacting with police officers and other individuals in positions of power. With the recent increased exposure of racialized violence against Black people at the hands of police and vigilantes in the United States, many parents of young Black children now feel especially compelled to initiate these conversations to equip their children with the necessary knowledge to protect themselves when interacting with police officers. Black parents bear the unjust burden of striking a balance between alerting their children of possible harm while also not villainizing every member of law enforcement their child may encounter. This qualitative study examines "the Talk" occurring between 45 Black American parents and their young school-age children via observational methods. Findings of this study help to illuminate this critically important experience that characterizes Black familial processes and particularly the plight of parents socializing Black children. Implications for parent education and clinical interventions are also provided.